2009
DOI: 10.3748/wjg.15.321
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of four strains of probiotics on experimental colitis in mice

Abstract: The four strains of probiotics have beneficial effects on experimental colitis in mice. E. faecalis has a better effect on DSS-induced experimental colitis in mice than the other three strains. Supplement of probiotics provides a new therapy for UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
21
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 26 publications
9
21
0
2
Order By: Relevance
“…The intestinal anti-inflammatory/immunomodulatory properties of Lactobacillus sp. have been previously described in experimental models of colitis (7,8). Our MPO results are in accordance with previous studies of Chen et al (8) showing Ͼ50% (2-fold) reduction in MPO levels by L. acidophilus in Balb/c mice treated for 5 days with 5% DSS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The intestinal anti-inflammatory/immunomodulatory properties of Lactobacillus sp. have been previously described in experimental models of colitis (7,8). Our MPO results are in accordance with previous studies of Chen et al (8) showing Ͼ50% (2-fold) reduction in MPO levels by L. acidophilus in Balb/c mice treated for 5 days with 5% DSS.…”
Section: Discussionsupporting
confidence: 93%
“…have been previously described in experimental models of colitis (7,8). Our MPO results are in accordance with previous studies of Chen et al (8) showing Ͼ50% (2-fold) reduction in MPO levels by L. acidophilus in Balb/c mice treated for 5 days with 5% DSS. The almost complete prevention of increased MPO levels by L. acidophilus observed in L. acidophilus ϩ DSS mice could be due to the lower concentration of DSS (3%) used in our current studies compared with 5% DSS used by Chen et al In addition, loose fecal pellets were observed in the DSS mice, but not in any other group, including the L. acidophilus ϩ DSS mice.…”
Section: Discussionsupporting
confidence: 93%
“…Probiotic foods containing LAB have been proposed as a natural alternative to improve the general health status, preventing various gastrointestinal disorders such as gastric ulcers and inflammation related to H. pylori infection, gastrointestinal infections (Lebeer et. al., 2010) or antibiotic-associated diarrhea (Chen et. al., 2009;Gill & Guarner, 2004;Penner et.…”
Section: Lactic Acid Bacteria In Gastritismentioning
confidence: 99%
“…The results of Chen and colleagues 71 show that in the same model of colitis, different strains of probiotics are capable of achieving similar effects. When the model of colitis is changed however, so does the aetiology of the disease and the effects of probiotics.…”
Section: Therapeutic Effects Of Probiotics In Animalsmentioning
confidence: 97%
“…In addition to their prophylactic study, Mane and colleagues 55 ] were able to reduce, at least in part, the effects of colitis. Effects of DSS-induced colitis included: body mass loss, 70,71 higher disease activity index scores, 71 shortening of the colon, 70 reduced ZO-1 mRNA expression in IECs, 70 increased leukocyte infiltration in the colon, 70 increased Na + absorption in the colonic mucosa, 70 increased MPO activity 71 and colonic IL-1β production, coupled with lower IL-4 production. 71 All strains were effective in reducing the effects of colitis, EcN and E. faecalis proved most effective.…”
Section: Therapeutic Effects Of Probiotics In Animalsmentioning
confidence: 99%